Peran Guru Mata Pelajaran IPS dalam Menanamkan Sikap Sopan Santun dan Tanggung Jawab Siswa Kelas VII SMP Islam Al Hidayah Samir Ngunut Tulungagung - Dilla Minhatul Maula; Ikfi Khoulita (STIKes Ibnu Sina Ajibarang, 2025)
The purpose of this study was to determine the role of social studies teachers in instilling politeness and responsibility in class VII students of SMP Islam Al Hidayah Samir Ngunut Tulungagung. This study uses a descriptive qualitative method. Data collection was carried out through observation, interviews and documentation. The data analysis technique used the Miles and Huberman concept with three stages of analysis, namely data reduction, data presentation and then drawing conclusions. Checking the validity of the findings was done by extending participation, consistency of observation, and data triangulation using The results of this study found five roles of teachers in instilling politeness and responsibility in class VII students of SMP Islam Al Hidayah Samir Ngunut Tulungagung. The supporting factors for social studies teachers in instilling politeness and responsibility in students are social studies teachers, school policies, and parents. While the inhibiting factors for social studies teachers in instilling politeness and responsibility in students are the students themselves and their parents.